An age of our own making a reader reflecting on three topical issues of our time : coloniality and ecology, immunity and migration, as well as globalization and citizenship : publikationen reflekterer over tre aktuelle emner : kolonialitet og økologi, immunitet og migration samt globalisering og medborgerskab - Ovesen, Solvej Helweg 1974-; Ndikung, Bonaventure Soh Bejeng 1977- (The Green Box, 2016)
An Age of Our Own Making is a reader published in relation to the exhibition of the same title in Denmark edited by Bonaventure Soh Bejeng Ndikung and Solvej Helweg Ovesen. The exhibition, which is part of the Danish IMAGES art programme, unfolds in three separate exhibition parts, Reflections I-III, inviting viewers to reflect on how we want to co-exist in this world, both with the human and non-human species — beyond current tendencies of overprotection and unsustainable privileges. The reader features texts by Dipesh Chakrabarty, Vyjayanthi Rao, Henrik Vigh, AbdouMaliq Simone, Roberto Esposito and Jane Bennett. It takes up the challenge to investigate some of the characteristics that make up an age defined by humanity and will be subdivided into three main reflection trajectories: the redefinition of materials in an ecological and postcolonial context; the concept of over-protection (in contradistinction to migration) inherent to the sovereignty of the nation state; and finally the entrepreneurial enactment of citizenship. Participating artists in the exhibition: Reflection I: Ibrahim Mahama, Eko Prawoto, Sammy Baloji, Ehsan Ul Haq, Angela Melitopoulos & Angela Anderson, Georges Adéagbo, Jems Robert Koko Bi, Julie Djikey, Jean Katambayi Mukendi, Misheck Masamvu, Hamed Ouattara, Reflection II: Athi-Patra Ruga, Bernard Akoi-Jackson, Ato Malinda, Aman Mojadidi, Mwangi Hutter, Amy Lee Sanford, Moe Satt, Urnamo, Nathalie Bikoro, Harold Offeh. Reflection III: Moshekwa Langa, Ibrahim Mahama, Kamal Aljafari, Tita Salina & Irwan Ahmett
"An age of our own making", an exhibition in Holbæk, Roskilde and Copenhagen, unfolds in three separate exhibition parts, Reflections I-III, opening one after the other in three different Danish cities. - Reflection I, Holbæk: The Life of Materials. On Another Nature and Ecology, 14 May - 15 August 2016; Reflection II, Roskilde: The Route that Tempts the Traveler to Test Gravity. Notes on Immunisation, ACTS 25 June - 26 June, Roskilde Festival 26. June - 2. July 2016; Reflection III, Copenhagen: An Age of Our Own Making - On Agency and Enacting Citizenship, 15 September 2016 - 8 January 2017
Edition/oplag: 1000
Keywords: Kunst; Ökologie; Postkolonialismus; Migration; Globalisierung; Ausser-Europäisch; Dänemark; Holbek Biennale; Ausstellungskatalog -- 14.05.2016-15.08.2016 -- Holbaek; Ausstellungskatalog -- 25.06.2016-26.06.2016 -- Roskilde; Ausstellungskatalog -- Kunsthal Charlottenborg -- 16.09.2016-15.01.2017 -- Kopenhagen; Aufsatzsammlung